2014
DOI: 10.1002/ejhf.178
|View full text |Cite
|
Sign up to set email alerts
|

Different regions of latest electrical activation during left bundle‐branch block and right ventricular pacing in cardiac resynchronization therapy patients determined by coronary venous electro‐anatomic mapping

Abstract: AimCurrent targeted left ventricular (LV) lead placement strategy is directed at the latest activated region during intrinsic activation. However, cardiac resynchronization therapy (CRT) is most commonly applied by simultaneous LV and right ventricular (RV) pacing without contribution from intrinsic conduction. Therefore, targeting the LV lead to the latest activated region during RV pacing might be more appropriate. We investigated the difference in LV electrical activation sequence between left bundle-branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…10,21,32 Recently, it has been demonstrated that activation mapping of the CS by EAMS can be used to guide LV lead placement to regions of delayed activation, and that the site with the latest electrical activation often does not correspond to the site of conventional "anatomical" LV lead placement, which targets a lateral CS branch regardless of the presence of myocardial scars or the type of conduction disturbance. 33,34 This study confirmed that, in the majority of cases, the latest electrical activation is recorded in mid-basal segments of the lateral LV wall. However, in a significant minority of patients, the most delayed activation was recorded in anterior or apical positions.…”
Section: Guiding LV Lead Positioningsupporting
confidence: 82%
See 1 more Smart Citation
“…10,21,32 Recently, it has been demonstrated that activation mapping of the CS by EAMS can be used to guide LV lead placement to regions of delayed activation, and that the site with the latest electrical activation often does not correspond to the site of conventional "anatomical" LV lead placement, which targets a lateral CS branch regardless of the presence of myocardial scars or the type of conduction disturbance. 33,34 This study confirmed that, in the majority of cases, the latest electrical activation is recorded in mid-basal segments of the lateral LV wall. However, in a significant minority of patients, the most delayed activation was recorded in anterior or apical positions.…”
Section: Guiding LV Lead Positioningsupporting
confidence: 82%
“…Although in the majority of cases the region of latest ventricular activation is the basal lateral LV wall, significant variability among patients exists, especially in the presence of myocardial scars or intraventricular conduction delays other than left bundle branch block . Recently, it has been demonstrated that activation mapping of the CS by EAMS can be used to guide LV lead placement to regions of delayed activation, and that the site with the latest electrical activation often does not correspond to the site of conventional “anatomical” LV lead placement, which targets a lateral CS branch regardless of the presence of myocardial scars or the type of conduction disturbance . This study confirmed that, in the majority of cases, the latest electrical activation is recorded in mid‐basal segments of the lateral LV wall.…”
Section: Discussionmentioning
confidence: 99%
“…Although RV pacing resembles intrinsic LBBB, certain differences regarding ventricular activation exist. These differences were reported in clinical studies employing electro‐anatomic mapping where electrical ventricular activation patterns during RV pacing and intrinsic LBBB were compared in order to examine potential consequences for cardiac resynchronization therapy . This different activation pattern may partly explain the deviation between the modified QT‐interval and the intrinsic QT‐interval.…”
Section: Discussionmentioning
confidence: 97%
“…These differences were reported in clinical studies employing electro-anatomic mapping where electrical ventricular activation patterns during RV pacing and intrinsic LBBB were compared in order to examine potential consequences for cardiac resynchronization therapy. 16,17 This different activation pattern may partly explain the deviation between the modified QT-interval and the intrinsic QT-interval. Consequently, the results of the present study can only be transferred with caution to patients with intrinsic LBBB although the novel formula was already examined in a small cohort of these patients.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Patients in our study were less symptomatic and more likely to receive optimal medical therapy. We included only patients with LBBB or wide‐paced QRS complex, in whom the latest electrical activation usually occurs in the LV non‐apical posterolateral region . In the control group of ImagingCRT, we targeted LV lead positioning towards non‐apical posterolateral segments with late electrical activation, thereby employing an approach associated with improved CRT outcome and included in the current guidelines .…”
Section: Discussionmentioning
confidence: 99%